Leadership in Local Government: 'No Girls Allowed'. Issue 2 (23rd June 2014) - Hutchinson, Jacquie; Walker, Elizabeth; McKenzie, Fiona Haslam
Abstract : This article explores the under‐representation of women at the Chief Executive Officer (CEO) levels of Western Australian (WA) local government. It draws on data collected from 21 second tier senior women managers about their perceptions and experiences of leadership within the sector, as well as their aspirations for CEO appointment. By applying critical gender analysis to the data, gender and specifically masculinity emerges as a significant and valued leadership attribute. While this analysis is not unique to local government, what sets the sector apart is its apparent disinterest in examining the reasons for, or the impacts of this continued leadership stereotype when at the same time Australian public and private institutions are challenging these traditional leadership models. This article points to fundamental weaknesses in the formal power structures and processes of local government that support deeply embedded biases about leadership. Perhaps the most significant contributor to these outcomes that emerged from the study is the apparent unencumbered power of Mayors and elected members over all aspects of CEO employment, especially recruitment.